Assessing the effect of longitudinal multiple subsidies on firm performance in the presence of neighbour interactions: A case study in the hotel industry - Roberto Gabriele; Enrico Tundis (European Regional Science Association (ERSA), 2015)
A Structural Marginal Model and Inverse Probability of Treatment Weighting (IPTW) estimation strategy is proposed in a dynamic 2-dimensional treatment setting in order to identify and estimate both the direct and the indirect average treatment effects of a policy over time. This approach is used to assess the effect of public capital subsidisation on the competitiveness of firms in the hotel sector in a place-based subsidisation public policy. A positive effect of the policy is estimated on several hotel performance indicators. Moreover, we found that a hotel?s performance depend on whether many or few hotels in its own destination are subsidised.
Keywords: 330; longitudinal multiple treatments; counterfactual methods; IPTW estimation